Optimal deficit-spending in a liquidity trap with long-term government debt - Charles De Beauffort (National Bank of Belgium, 2022)
When the government issues long-term bonds, the optimal time-consistent fiscal and monetary policy is to consolidate debt in a liquidity trap by increasing taxes and by taming public spending. This prescription is at odds with large deficit-spending undertaken in the US during previous liquidity trap episodes. In this article, I show that accumulating debt turns optimal with long-term bonds and flexible wages if labor taxes are kept constant or if monetary policy is conducted non optimally. Moreover, even when labor taxes fluctuate and policy is fully coordinated, optimal deficit-spending in a liquidity trap emerges in a medium-scale model with sticky wages and rule-of-thumb consumers. In this case, debt consolidation occurs only after the nominal interest rate has lifted-off the zero lower bound, in accordance with conventional wisdom that a government should fix the roof while the sun is shining
Keywords: E43; E52; E62; E63; 330; Optimal Time-Consistent Policy; Distortionary Taxation; Liquidity Trap; Fiscal and Monetary Policy; Sticky Wages; Rule-of-Thumb Consumers